Algae and cyanobacteria colonizing toxic soils on coal-mining dumps - Hrčková, Kristýna (Jihočeská univerzita, 2008)
Species composition of soil algal and cyanobacterial communities was investigated in thirteen sites of different toxicity of spoil material on dumps in the Sokolov mining area (Czech Republic). The adaptation ability of various algal and cyanobacterial species to live in toxic environment and the effect of different amendments (wooden coal, organic matter, dolomitic limestone) of toxic soils were tested both in laboratory and field experiments. According to results, species composition corresponded to environmental characteristic (pH, conductivity, substrate type). Some green unicellular algae grew successfully in extracts from the most toxic substrate and seemed to be well adapted to low pH conditions. Results indicate that increase of pH is a basic precondition for the establishment of more diverse and abundant algal flora in highly acidic sites.
Algae and cyanobacteria colonizing toxic soils on coal-mining dumps
Keywords: soil algae; soil cyanobacteria; succession; colonization; toxicity; dumps; Sokolov mining district; soil algae; soil cyanobacteria; succession; colonization; toxicity; dumps; Sokolov mining district